Pengaruh Keluarga Broken Home terhadap Perkembangan Moral dan Psikososial Siswa Kelas V SDN 1 Sumberbaru Banyuwangi - Rima Trianingsih; Isna Nurul Inayati; Faishol Riza (STKIP AL HIKMAH SURABAYA, 2019)
Teacher daily observation show that students often do rowdy, seeking attention with do the bad something and difficult to control is a child of the broken home family. It is then encouraged to conduct research with the objectives to undertake a deeper case study on the influence of broken home family against the moral and psychosocial development of grade V students of SDN 1 Sumberbaru. The study used a qualitative approach with case study design. Participants in this study were chosen with purposive samples, so that two students from the fifth grade of SDN 1 Sumberbaru were M.J.S and M.K.L. The data analysis techniques use thematic analysis. Research results describe that broken home family have influenced on moral and psychosocial development of participants. It can be described as bad moral behavior that arises: make mistakes and do not want to apologize; often do not obey the school order; and seek attention by making noise during lesson hours. The behavior of his psychosocial development is the following: not the spirit of learning a new experience; the child is not confident; and often compare herself with friends.